Enhancing restoration success of rare plants in an arid-tropical climate through water-saving technologies: a case study of Scalesia affinis ssp. brachyloba in the Galapagos Islands - Plunkett,Esme; Negoita,Luka; Sevilla,Christian; Velasco,Nicolás; Jaramillo Díaz,Patricia (PeerJ, 2023)
Arid tropical archipelagos, such as the Galapagos Islands, host a high concentration of endemic plant species, many of which require restoration intervention to recover from past environmental degradation. Water-saving technologies (WSTs) have potential for hastening restoration by providing plants with additional water during the early stages of growth. However, it remains unclear whether such technologies provide an advantage for plant species of arid-tropical regions. This study examined the effect of the water-saving technology Groasis Waterboxx® (Groasis) on the rare endemic plant species Scalesia affinis ssp. brachyloba during early stages of restoration. Survival was monitored for 374 individuals planted across six sites on Santa Cruz Island, Galapagos (326 with technology and 48 as controls). Kaplan-Meier survival analysis showed that the use of Groasis reduced mortality during the first two years of the seedling survival. A mixed-effect logistic regression that modelled plant survival as a function of total precipitation, maximum temperature, and WST treatment (Groasis and no-technology control) found that despite low overall survival rates, plants grown with Groasis exhibited a three-fold higher predicted survival by the end of the 3.7 year duration of the study. Finally, through a resampling method, we demonstrate that the effect of the WST treatment is not dependent on the unbalanced design typical of a restoration project framework. We conclude that water-saving technologies such as the Groasis Waterboxx® can enhance survival of rare plant species such as S. affinis ssp. brachyloba in restoration programs in arid-tropical regions.
Keywords: Ecological restoration; Galapagos; Scalesia affinis; Groasis Waterboxx; Endemic; Plants; Water-saving technologies; Islands